2013
DOI: 10.4049/jimmunol.1203340
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Independent Modulation of Experimental Autoimmune Encephalomyelitis in ADAP-Deficient Mice

Abstract: The adhesion- and degranulation-promoting adaptor protein (ADAP), expressed in T cells, myeloid cells, and platelets, is known to regulate receptor-mediated inside-out signaling leading to integrin activation and adhesion. In this study, we demonstrate that, upon induction of active experimental autoimmune encephalomyelitis (EAE) by immunization with the myelin oligodendrocyte glycoprotein35–55 peptide, ADAP-deficient mice developed a significantly milder clinical course of EAE and showed markedly less inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…1 A, left). In agreement with our observation, previous studies suggest that a deficiency of VAV1 or ADAP ameliorates myelin oligodendrocyte glycoprotein peptide (MOG 35–55)–induced EAE, a mouse model that mimics human MS (Korn et al, 2003; Engelmann et al, 2013). Because Mst1 binds to the RapL–Rap1 complex, whereas DOCK8 is the key downstream effector of Mst1 (Mou et al, 2012), we asked whether DOCK8 influenced the pathogenesis of MS/EAE.…”
Section: Resultssupporting
confidence: 93%
“…1 A, left). In agreement with our observation, previous studies suggest that a deficiency of VAV1 or ADAP ameliorates myelin oligodendrocyte glycoprotein peptide (MOG 35–55)–induced EAE, a mouse model that mimics human MS (Korn et al, 2003; Engelmann et al, 2013). Because Mst1 binds to the RapL–Rap1 complex, whereas DOCK8 is the key downstream effector of Mst1 (Mou et al, 2012), we asked whether DOCK8 influenced the pathogenesis of MS/EAE.…”
Section: Resultssupporting
confidence: 93%
“…We have previously shown that conventional ADAP k.o. mice develop much milder EAE than wild-type mice, however, most likely mainly due to a T cell-independent mechanism (25). Therefore, on the basis of our observed effects of specific ADAP k.o.…”
mentioning
confidence: 59%
“…The induction of EAE in ADAP-deficient recipient mice reconstituted with wild-type bone marrow also revealed milder EAE, suggesting a mainly T cell-independent mechanism. These data indicated possible effects of radioresistant cells or indirect effects of other hematopoietic cells (25).…”
mentioning
confidence: 81%
“…In animal models of heart and intestinal allograft transplantations, ADAP deficiency improved the survival of the grafts significantly, emphasizing the crucial role of ADAP in the induction of T cell-mediated immunity [19,20]. Moreover, we have demonstrated that ADAP deficiency ameliorates experimental autoimmune encephalomyelitis in mice, a model strongly relying on CD4 + T cells, although surprisingly, not in a T cell-intrinsic manner [21]. Interestingly, a recent finding also suggests a more regulatory role for ADAP.…”
Section: Introductionmentioning
confidence: 61%